Deep-living and diverse Antarctic seaweeds as potentially important contributors to global carbon fixation - Leigh W. Tait; Caroline Chin; Wendy Nelson; Steve George; Peter Marriott; Richard L. O’Driscoll; Miles Lamare; Victoria S. Mills; Vonda J. Cummings (Communications Earth & Environment, 2024)
Abstract Global models predict that Antarctica has little suitable habitat for macroalgae and that Antarctic macroalgae therefore make a negligible contribution to global carbon fixation. However, coastal surveys are rare at southern polar latitudes (beyond 71° S), and here we report diverse and abundant macroalgal assemblages in un-navigated coastal habitats of the Ross Sea from 71.5°–74.5° S. We found extensive macroalgal assemblages living at depths >70 m and specimens of crustose coralline algae as deep as 125 m. Using global light modelling and published photosynthetic rates we estimate that Antarctic macroalgae may contribute between 0.9–2.8 % of global macroalgal carbon fixation. Combined, this suggests that Antarctic macroalgae may be a greater contributor to global carbon fixation and possibly sequestration than previously thought. The vulnerability of these coastal environments to climate change, especially shifting sea ice extent and persistence, could influence Southern Ocean carbon fixation and rates of long-term sequestration.